Does Money Illusion Matter? An Experimental Approach - Ernst Fehr; Jean-Robert Tyran (Institute for the Study of Labor (IZA), 2000)
Money illusion means that people behave differently when the same objective situation is represented in nominal terms rather than in real terms. This paper shows that seemingly innocuous differences in payoff representation cause pronounced differences in nominal price inertia indicating the behavioral importance of money illusion. In particular, if the payoff information is presented to subjects in nominal terms, price expectations and actual price choices after a fully anticipated negative nominal shock are much stickier than when payoff information is presented in real terms. In addition we show that money illusion causes asymmetric effects of negative and positive nominal shocks. While nominal inertia is quite substantial and long-lasting after a negative shock, it is rather small after a positive shock.
Keywords: E32; E52; C92; 330; Money illusion; nominal inertia; sticky prices; non-neutrality of money; Geldillusion; Experiment; Theorie